Kesiapan Penerapan Hedging Syariah pada Perbankan Indonesia - Yunisa Fitriana (Al-Tijary, 2019)
sharia hedging/ hedging transactions based on DSN Fatwa No. 96 by using sharia commodity instruments is a new thing in Indonesia, so that more in-depth studies are needed to analyze the readiness of Islamic banks in implementing sharia hedging / hedging transactions on exchange rates based on DSN No. Fatwa. 96 for ‘aqd al-tahawwuth bi al-sil’ah (using sharia commodities).The research method used is a qualitative approach with survey and interview methods, based on (a) Total assets of Islamic Financial Institutions (LKS) / Sharia Business Units (UUS). (b) Availability of being a respondent. (c) Respondents know well the mechanism in the DSN Fatwa No. 96. The results of this study found that (1) Issuance of DSN 96 Fatwa for the third mechanism has not been applied by Islamic banking. (2) Regulators (BI, OJK and related regulators) have not been able to provide detailed regulations related to Islamic hedging / hedging. (3) Commodities that can be transacted by the third mechanism are limited to coal, gold, bauxite.